Repurposing Kinase Inhibitors as Antiviral Agents to Control Influenza A Virus Replication - Perwitasari, Olivia (Assay Drug Dev Technol, 2015)
Influenza A virus (IAV) infection causes seasonal epidemics of contagious respiratory illness that causes substantial morbidity and some mortality. Regular vaccination is the principal strategy for controlling influenza virus, although vaccine efficacy is variable. IAV antiviral drugs are available; however, substantial drug resistance has developed to two of the four currently FDA-approved antiviral drugs. Thus, new therapeutic approaches are being sought to reduce the burden of influenza-related disease. A high-throughput screen using a human kinase inhibitor library was performed targeting an emerging IAV strain (H7N9) in A549 cells. The inhibitor library contained 273 structurally diverse, active cell permeable kinase inhibitors with known bioactivity and safety profiles, many of which are at advanced stages of clinical development. The current study shows that treatment of human A549 cells with kinase inhibitors dinaciclib, flavopiridol, or PIK-75 exhibits potent antiviral activity against H7N9 IAV as well as other IAV strains. Thus, targeting host kinases can provide a broad-spectrum therapeutic approach against IAV. These findings provide a path forward for repurposing existing kinase inhibitors safely as potential antivirals, particularly those that can be tested in vivo and ultimately for clinical use.